1999
DOI: 10.1002/(sici)1520-6394(1999)9:3<131::aid-da5>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the safety and tolerability of two dose regimens of buspirone in patients with persistent anxiety

Abstract: Buspirone is an azapirone with 5-HT1A partial agonist activity which has demonstrated efficacy in the treatment of generalized anxiety disorder, commonly referred to as persistent anxiety. In this meta-analysis report, safety results from two studies comparing buspirone 15 mg twice daily (BID) with buspirone 10 mg three times daily (TID) in patients with persistent anxiety are presented. In the study protocols, qualified patients completed a 7-day placebo lead-in phase and were randomized to receive buspirone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We used treatment period of 6 weeks based on the previous 6‐week buspirone trial studies in generalized anxiety disorder (GAD) 29,30 . As noted in the IHS guidelines, however, only the effects of sufficient duration (at least 3 months) are clinically relevant.…”
Section: Commentsmentioning
confidence: 99%
“…We used treatment period of 6 weeks based on the previous 6‐week buspirone trial studies in generalized anxiety disorder (GAD) 29,30 . As noted in the IHS guidelines, however, only the effects of sufficient duration (at least 3 months) are clinically relevant.…”
Section: Commentsmentioning
confidence: 99%
“…Dizziness or light-headedness is a side effect reported commonly with 5HT 1A agonist drugs with an incidence of up to 20-80% (Driver et al 1995;Sramek et al 1999;Robinson et al 2003), far exceeding the reported incidences after other psychotropic drugs. It is often assumed that because this dizziness is worse on standing, it is caused by postural hypotension.…”
mentioning
confidence: 87%
“…The initial dose is 5 mg two to three times daily, which may be progressively increased up to 30 mg daily. Such side effects as dizziness, headache, and nausea are usually transient and subside as treatment continues [89]. Buspirone has been shown to stimulate respiration experimentally [36,58] and in patients with lung disease [23].…”
Section: Buspironementioning
confidence: 99%